Findings for iGlarLixi versus BIAsp 30 confirmed in groups of people with type 2 diabetes with different biomedical characteristics. Issue 3 (23rd November 2022) - Home, Philip D.; McCrimmon, Rory J.; Rosenstock, Julio; Blüher, Matthias; Pegelow, Katrin; Melas‐Melt, Lydie; Djaballah, Khier; Giorgino, Francesco; ,
Abstract: Aim: To report prespecified and post hoc analyses of the SoliMix dataset exploring the impact of baseline participant characteristics on the original SoliMix study outcomes, to enable informed treatment choices for people with different biomedical characteristics. Methods: SoliMix (EudraCT 2017‐003370‐13) compared once‐daily iGlarLixi (a fixed‐ratio combination of insulin glargine 100 U/mL and the glucagon‐like peptide‐1 receptor agonist lixisenatide) with twice‐daily BIAsp 30 (30% insulin aspart and 70% insulin aspart protamine). In this analysis, the original primary outcomes of noninferiority of iGlarLixi versus BIAsp 30 in terms of glycated haemoglobin (HbA1c) change and superiority in terms of body weight change, together with change in basal insulin dose and hypoglycaemia outcomes, were investigated by baseline age, duration of diabetes, insulin dose, HbA1c level, body mass index (BMI), and renal function. Results: No evidence of difference in comparative treatment effect was detected across baseline age, duration of diabetes, insulin dose, HbA1c level, BMI and renal function subgroups for any endpoint (all heterogeneity P > 0.05), except American Diabetes Association Level 2 hypoglycaemia event rate when stratified by insulin dose ( P = 0.011), which may be a chance difference given multiple testing and the small numbers of Level 2 events. Conclusions: Treatment effects of iGlarLixi were consistent irrespective of baseline HbA1c, insulin dose, BMI, age, duration of diabetes and renal function, supporting the use of iGlarLixi as an efficacious and well‐tolerated treatment option in people with type 2 diabetes with a wide range of biomedical characteristics.